Vous êtes sur la page 1sur 8

3) encontrar las derivadas de la funciones siguientes :

{ {

]}}

a) f(x) = cos sen arctang ln 3 (x 2 + 3x)


u
= 2x + 3
x

2
sea : u = x + 3x

{ {

f(x) = cos sen arctang ln(U)3


m 1
=
u
u
f(x) = cos{ sen{ arctang m 3

]}}

sea :m= ln(U)

[ ]

sea : n = arctang m 3

]}}

n
m3
3m 2
=
=
m 1 m 6 1 m 6

f(x) = cos{ sen{ n}

sea : p = sen{ n}

p
= cos(n)
n

f(x) = cos{ p}
sea : k = cos{ p}
f(x) = k

k
= sen(p)
p

y
=1
k

Ordenando:
Y-k-p-n-m-u-x
y y k p n m u
=


x k p n m u x
3m2 1
y
(2 x + 3)
= (1)(sen( p ))(cos(n))
6
x
1 m u
3
2
y
= 1[ sen( sen(h)] cos(arctan g (m3 )) u
x
1 1

u6

(2 x + 3)

1 3u 6

( 2 x + 6)
y1 = 1 sen( sen(arctan g (m3 )) cos(arctan g ( 3 )) 6 6
u u (u 1)

3( x 2 + 3x) 4
1
1

(2 x + 6)
y1 = 1 sen( sen(arctan g ( 3 )) cos(arctan g ( 2
))
u
( x + 3x)3 ( x 2 + 3x)6 1

y1 = sen[ sen(arctan g (

f(x) = arcos3 tang 2 sec 2 log 4 4 x 2x

b)

3( x 2 + 3x) 4
1
1

( 2 x + 6)
]
))
cos(arctan
g
(
))

( x 2 + 3 x )3
( x 2 + 3x)3 ( x 2 + 3 x)6 1

)]}

sea : u = 4 x 2x

u
2
=
2
x
x

y = arcos 3 tang 2 sec 2 log 4 ( u )

t
1
sea : t = log 4 ( u )
= 4log 3 (u)log(e)
u
10
1

y = arcos 3 tang 2 sec 2 [ t ]

m
2
sea : m = sec [ t ]
= 2sec(t)(sec(t)tang(t))
t
1

y = arcos 3 tang 2 {m}

]}

tang 2 {m}
n
sea : n = tang {m}
=
(sec(m))
m
2

3
y = arcos {n}
1
2

sea : p = arcos 3 {n}

`p
1
= 3arcos 2 (n)

2
n
1 n

y
=1
p
Ordenado :
y =p

y-p-n-m-t-u
1

tang
{m} 4log 3 (u)log(e) 2 2

2
10

tang 2 sec 2 ( t ) 4log 3 (4 x - 2x)log(e) 2

x
1
2
2

= 3arcos (sec (t))


2

y
2
10

x
1
= 3arcos 2 (m)
2
y
1 n

tang 2 {sec 2 (log 4 (u)}


x
1
2
2
4
2
4
= 3arcos (sec (log (u))
{sec sec (log (u) } (a)
2
y
2

1 2 2

tang 2 sec 2 (log 4 2 2

x
1
x

2
4
= 3arcos 2 (sec2 (log 4 (4 x - 2x))
sec sec (log (4 x - 2x) (a )
2
y
2
1 2 2


c)

{ [

]}

{ {

}}}

h(x) = tang arcsen cos arccosec(x 2 + sen 2x 3 )

u
1 6x
3x 2
= 2x +
=
x
2 2x 3
2x 3
h(x) = tang{ arcsen{ cos{ arccosec(u )}}}

sea : u = x 2 + sen 2x 3

sea : t = arccosec(u)

t
1
=
u
t t2 1

h(x) = tang{ arcsen{ cos{ t}}}

m
= sen (t)
t
h(x) = tang{ arcsen{ m}}
n
1
sea : n = arcsen{ m}
=
m
1 - m2
sea : m = cos{ t}

h(x) = tang(n)
sea : p = tang(n)
h(x) = p

x
=1
y

p
= sec 2 (n)
n

Ordenando:
y-p-n-m-t-u
y p n m t u
y
=
p
n m t u x
x

{ [

y
= tang arcsen cos arccosec(x 2 + sen 2x 3
x

y
1
= sec 2 ( n )

2
x
1 n

3x 2

2
3

t
t

2x

]}}

3x 2

2
3
2x

arcosec(u) arcosec (u) 1

3x 2
y
1
1

= sec 2 ( arcsen(cos(t) )
3
1 cos 2 (arcosec(u)) arcosec(u) arcosec2 (u) 1
x

2x

....
arcosec(x 2 + sen 2 x 3 )

y
1
= sec 2 ( arcsen(m))

2
x
1 cos t

d)

...

J(x) = ln 3 5 e 2 x + log 4 (x)

u
1
2
sea : u = e 2 x + log 4 (x)
= e2 x
+ 4log3 (x) ( log(e))

x
2
2 x
J(x) = ln 3 5 u

[ ]
t
sea : t = [5 u ]
=
u

1
5 4
5 u

J(x) = ln 3 (t)
sea : m = ln 3 (t)
J(x) = m

m 3ln 2 (t) 3ln(t)


=
=
t
t
t

y
=1
m

Ordenado:
y-m-t-u
y y m t u
=


x m t u x

y
3 ln(t ) 1
= (1)

x
t 55 u 4

5
y 3 ln( u )
=
x 5 u

5 2
5 e

(e 2 x )(2 / x ) + 4 log3 ( x )(log e)(1 / x)

1
(e 2 x )(2 / x ) + 4 log3 ( x)(log e)(1 / x)

x + log 4 ( x )

2
x
4
+ log ( x) )
y 3 ln( e
1
(e 2 x )(2 / x ) + 4 log3 ( x )(log e)(1 / x)
=

x 5 2 x
4

4 ( x ) 2 x

e
+
log
4

55 e
+
log
(
x
)

e)

]]
cos [log (2 x )]

k(x) = ln 2 ( x ) + cos 4 log 3 (2 x )


sea : u =

x+

por el metodo de cadena

k1 (x) = cos 4 log 3 (2 x )


sea : u1 = 2 x
k1 (x) = cos 4 [ u1 ]

u
x

u1
1
=
x
x

sea : t1 = cos 4 [ u1 ]

t1
1
= log(e)
u1
u1

k1 (x) = cos 4 (t1 )3


sea : m1 = ( t1 )
3

m1
= 3(t1 ) 2
t1

k1 (x) = cos 4 (m1 )


sea n1 = cos 4 (m1 )

n1
= 4sen 3 (m1 )( sen(m1 ) )
m1

Ordenando :
y y n1 m1 t1 u1

x
n1 m1 t1 u1 x

y
1 1
= (1) 4sen 3 (m1 ).(-sen(m1 )) (3(t1 ) 2 )
log(e)

x
u1

y
6 log e 1
= 4sen 3 (3(t1 ) 2 ).(- sen(3(t1 ) 2 ) )( 3log(u1 ) )

x
2 x x
y
6 log e
= 4sen 3 (3(t1 ) 2 )3( log(u1 ) )

x
2x

][

y
log(e)
= 4sen 3 (3log 6 (u1 ) 3log 6 (2 x )
x
2x

][

][

y
log(e)
= 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )
x
2x
y
log(e)
= 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )
x
2x

][

] log(e)
2x

][

] log(e)
2x

u1 =

x + 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )

u1 =

x + 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )

][

u
1
log(e)
=
+ x + 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )
x
2x
2 x
t
1 2ln(u)
K(x) = ln 2 (u)
= 2ln(u) =
u
u
u

u =

K(x) = t

y
=1
t

Ordenado :
y t u x
u y t u
=

x t u x

][

u
log(e)

2ln(u) 1
= (1)
+ x + 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )

x
u
2x

2 x

u
2ln( x ) + cos 4 (3log 6 (2 x )
1

log(e)

=
+ x 4sen 4 (3log 6 (2 x ) 3log 6 (2 x )

4
6
x
2
x
2x

x + cos (3log (2 x )

f)

][


Y(x) = arcsen3 4

sea : u = 4

3
3

cos( x 2 ) 1

cos( x 2 ) +1

cos( x 2 ) 1

cos( x 2 ) 1
u 33 cos( x 2 ) 1

=
x
cos( x 2 ) +1
cos( x 2 ) 1
4
4

cos( x 2 ) +1

3
3

2 xsenx 2

1
2 xsenx 2
=
=
2
2
cos( x ) 1 cos( x 2 ) 1
44 cos( x ) 1
3
4
12

cos( x 2 ) +1
cos( x 2 ) +1 cos( x 2 ) +1

Y(x) = arcsen3 [u ]
sea : t1 = arcsen3 [u ]
Y(x) = t

t1
1
= 3arcsen[u ]

2
u1
1 u

y
=1
t

Ordenando :
y y t u
=

x t u x

y
= (1)3arcsen[u ]

3
y
= 3arcsen
3
x

g)

1
1

2
2
1 u
cos( x ) 1 cos( x 2 ) 1
3
4
12

cos( x 2 ) +1 cos( x 2 ) +1

cos( x 2 ) 1

cos( x 2 ) +1

3
3

1
1

2
2
cos( x 2 ) 1 123 cos( x ) 1 4 cos( x ) 1

cos( x 2 ) +1 cos( x 2 ) +1

cos( x 2 ) +1

cosh 2 x 2 1
L(x) = senh3

tangh 2 x 2 1

sea : u =

cosh 2 x 2 1
tangh 2 x 2 1

cosh 4 x 2 1
senh 2 x 2 1

)(

) (

)(

u
cosh 4 x 2 1 senh 2 x 2 1 cosh 4 x 2 1 senh 2 x 2 1

=
2
x
senh 2 x 2 1

2x
2x
2

senh x 1
4cosh 3 x 2 1

senh 2 x 2 1

2senh x 2 1

cosh x 2 1

cosh 4 x

2 x 2 1

2 x 2 1
W=
2

senh 2 x 2 1

) (

) (

)(

4x
senh x 2 1 + 2 (x) cosh 4 x 2 1

cosh 3 x 2 1 senh 3 x 2 1

x 2 1
x 2 1
W =
2
senh 2 x 2 1

L(x) = senh 3 (u)


sea : t = senh 3 (u)

t
= 3senh 2 (u)cosh(u)(1)
u

Ordenando :
y y t u
=

x t u x
4
2

cosh 2 x 2 1

y
cosh cosh x 1 [ W ]
= (1) 3senh 2
tangh 2 x 2 1
senh 2 x 2 1
x